Increased frequency of hospital admissions with active systemic lupus erythematosus disease activity defined by two different disease activity indices: A cohort study. (June 2023) - Wang, Chun-Lung; Koo, Malcolm; Hsu, Chia-Wen; Lu, Ming-Chi
The objective of this cohort study was to evaluate the association between the frequency of hospital admissions and disease activity, as defined by two different disease activity measurements: the Systemic Lupus Erythematosus Disease Activity Score (SLE-DAS) and the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K), in adult patients with systemic lupus erythematosus (SLEs). Patients with SLE were recruited from the rheumatology outpatient department of a regional hospital in southern Taiwan. SLE-DAS and SLEDAI-2K were used to define SLE disease activity and the cause of hospital admissions was identified by a rheumatologist based on medical records. A generalized linear model (GLM) with gamma distribution and log-linked function was used to analyze variables associated with the frequency of admission. The mean frequency of hospitalization was 0.34 times per year for all-cause and 0.21 times per year for SLE-related admission. Multivariate GLM analysis showed that moderate/severe SLE disease activity defined by SLE-DAS was associated with an increased frequency of all-cause and SLE-related hospital admissions while adjusting for other covariates. Moderate/severe SLE disease activity defined by SLEDAI-2K was only significantly associated with an increased frequency of all-cause hospitalization. When steroid dosage was included in the model, moderate/severe SLE disease activity defined by the SLE-DAS remained significantly associated with SLE-related hospital admissions ( p = 0.032). In conclusion, disease activity defined by the SLE-DAS, but not SLEDAI-2K was associated with an increased frequency of SLE-related hospitalization. Steroid dosage, a lower educational level, and smoking were associated with an increased frequency of hospital admissions, whereas underweight and alcohol use were associated with a decreased frequency of hospital admissions. Rheumatologists should promptly control SLE disease activity of their patients, provide them with adequate health education, and maintain steroid doses to as low as possible to reduce the risk of hospital admissions.